Training on Introduction to Technology and Computer Operation for Village Officials in Adipuro, Magelang Regency: Indonesia - Tri Yusnanto; Kanafi; Sugeng Wahyudiono (PT FORMOSA CENDEKIA GLOBAL, 2022)
This community service has the aim of providing motivation, knowledge and basic skills or expertise to master computer and information technology in developing the skills and competencies of village officials. The lecture method aims to activate the enthusiasm of the participants to increase learning motivation as well as to explain computer technology concepts. Furthermore, the demonstration method is used when demonstrating work and learning processes, the operation of Windows and Microsoft Office. The training method is practicing directly how to assemble and operate the various applications used. Then this question-and-answer method provides time for participants to conduct consultations on how to overcome problems encountered when carrying out installation during training. Based on the activities that have been carried out, almost all participants, namely around 80%, are able to understand and practice well all the material presented during community service activities.